SCIENTIFIC PRODUCTION ON THE MENTAL HEALTH OF TRANSGENDER PEOPLE IN THE SCOPUS DATABASE: A BIBLIOMETRICS STUDY - Castilho, Francinéa de Nazaré Ferreira de; Carvalho, George Pinheiro; Nascimento, Marcia Helena Machado; Ferreira, Ilma Pastana (Cogitare Enfermagem, 2024)
Objective: to map scientific production on the mental health of transgender people, indexed in the Scopus database. Method: Bibliometric study, comprising the study of articles, including reviews, from January 2001 to June 2023, with analysis of indicators such as number of documents per year, language, journals most used, most productive authors, productivity of authors, affiliation of authorship, country of authors and keywords. Results: 988 documents were identified, concentrated in the years 2023 (9.8%), 2022 (17.2%), 2021 (18.8%), 2020 (12.7%), and 2019 (10.1%). The ten authors who have published the most on the subject are from the United States (90%). The journal with the highest number of articles was LGBT Health. The most used terms in the studies were: Female, Male, Transgender, Human, Humans, Adult, Transgender Persons, and Mental Health. Conclusion: There was a need for greater encouragement of publications in both Brazilian and international journals about the transsexual population.